DAYA SAING SAYUR HIDROPONIK DI KABUPATEN SAMBAS - Sari, Dian; Widi Wilujeng , Wilis; Dian Novita , Uray (Lembaga Kajian Ilmu Sosial dan Politik (LKISPOL), 2024)
The purpose of this study was to analyze competitiveness and formulate marketing strategies for hydroponic vegetable businesses in Sambas Regency. The benefit of this research is as information material for related parties, namely the hydroponic vegetable business and material for evaluation considerations to maintain the business. For other parties, the results of this study are expected to be a reference or reference material for readers in conducting further research. This research was conducted in Sambas Regency. The research method used in this research is a qualitative research method with a descriptive approach. Data processing and analysis techniques used descriptive qualitative methods, Porter's Diamond Theory and Porter's Five models. The results of the analysis of competitiveness using Porter's Diamond Theory, it can be seen that the level of competitive power of hydroponic vegetables is moderate, which means that it has enough competitiveness among fellow vegetable business actors. as well as resource factors with related and supporting industrial components. The alternative strategies chosen are low cost strategy, differentiation strategy and focus strategy.